On special weak free (semi)hypergroups - Morteza Jafarpour; Abdolah Chashiyani (Journal of Hyperstructures, 2013)
In this paper, we study some properties of special weak free (semi)hypergroups and we generalize the Nielsen-Schreier theorem for the class of special weak free hypergroups.